Distribution of Voltage-Gated Sodium Channel (Nav) Alleles among the Aedes aegypti Populations In Central Java Province and Its Association with Resistance to Pyrethroid Insecticides. - Sayono Sayono; Anggie Puspa Nur Hidayati; Sukmal Fahri; Didik Sumanto; Edi Dharmana; Suharyo Hadisaputro; Puji Budi Setia Asih; Din Syafruddin (PLoS ONE, 2016)
The emergence of insecticide resistant Aedes aegypti mosquitoes has hampered dengue control efforts. WHO susceptibility tests, using several pyrethroid compounds, were conducted on Ae. aegypti larvae that were collected and raised to adulthood from Semarang, Surakarta, Kudus and Jepara in Java. The AaNaV gene fragment encompassing kdr polymorphic sites from both susceptible and resistant mosquitoes was amplified, and polymorphisms were associated with the resistant phenotype. The insecticide susceptibility tests demonstrated Ae, aegypti resistance to the pyrethroids, with mortality rates ranging from 1.6%-15.2%. Three non-synonymous polymorphisms (S989P, V1016G and F1534C) and one synonymous polymorphism (codon 982) were detected in the AaNaV gene. Eight AaNaV alleles were observed in specimens from Central Java. Allele 3 (SGF) and allele 7 (PGF) represent the most common alleles found and demonstrated strong associations with resistance to pyrethroids (OR = 2.75, CI: 0.97-7.8 and OR = 7.37, CI: 2.4-22.5, respectively). This is the first report of 8 Ae. aegypti AaNaV alleles, and it indicates the development of resistance in Ae. aegypti in response to pyrethroid insecticide-based selective pressure. These findings strongly suggest the need for an appropriate integrated use of insecticides in the region. The 989P, 1016G and 1534C polymorphisms in the AaNaV gene are potentially valuable molecular markers for pyrethroid insecticide resistance monitoring.